Physico-chemical characteristics of groundwater around singrauli coalfield areas, singrauli district of madhya pradesh (India) - Sonkar A.K.; Jamal A. (My University, 2025)
Groundwater is contaminated around Singrauli coalfield area due to mining and industrial activities. The major cause of the contamination of ground water may be due to improper disposal of industrial waste. The aim of the present study was to assess the groundwater quality and also to have a statistical analysis of physicochemical parameters of groundwater around Singrauli coalfield region, Singrauli District of Madhya Pradesh (India).Eight groundwater samples were collected from the hand pump & Dug-wells located around Singrauli coalfields area during pre-monsoons and post monsoons seasons in the year 2018and analyzed for physicochemical parameters such aspH, TDS, EC, DO, Fluoride, Chlorides, Nitrate, Sulphate, Lithium, Sodium, Potassium, Magnesium and Calcium.A systematic calculation of the correlation coefficient has also been carried out between different analyzed parameters. © RASĀYAN. All rights reserved.